The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1200/jco.2004.10.155
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bortezomib for Patients With Advanced Renal Cell Carcinoma

Abstract: The results of this trial suggest that bortezomib has an antitumor effect in individual patients with metastatic RCC. The small proportion of patients who achieved a partial response does not support routine use in metastatic RCC. Efforts to identify the molecular profile associated with clinical response or combination therapy with interferon alfa or other novel agents, may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(100 citation statements)
references
References 12 publications
4
91
1
3
Order By: Relevance
“…Contrasting results were obtained in two Phase II trials at single institutions conducted in patients with advanced RCC [97,98] . Bortezomib was administered twice-weekly for 2 weeks of every 3 weeks in both the studies.…”
Section: Phase II Clinical Trialsmentioning
confidence: 99%
“…Contrasting results were obtained in two Phase II trials at single institutions conducted in patients with advanced RCC [97,98] . Bortezomib was administered twice-weekly for 2 weeks of every 3 weeks in both the studies.…”
Section: Phase II Clinical Trialsmentioning
confidence: 99%
“…In this setting, bortezomib (Velcade) was demonstrated to be effective in the treatment of multiple myeloma and non-Hodgkin's lymphoma, when taken alone or in combination with traditional anticancer drugs [3][4][5][6][7]. Similarly, preliminary studies indicated that proteasome inhibitors induce clinical responses in patients with acute leukemia, prostate cancer, renal cell carcinoma, neuroendocrine tumors, and in children solid tumors [8][9][10][11][12]. How proteasome inhibition translates into a potent cytotoxic effect in tumor cells is not fully understood, even though inhibition of NF-jB and deregulated expression of p53, caspases, Bcl-2 family members, CDC25 family proteins and cyclins were all proposed to be relevant in this context [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…22 This has been exploited in the therapy of malignancies in which tumor cells have been shown to have preferential sensitivity to the proapoptotic effects of proteasome inhibition. [23][24][25][26][27] Studies in murine tumor models 28,29 and small clinical studies 30,31 have shown activity against a spectrum of malignancies. In addition, bortezomib has recently been approved for the treatment of patients with relapsed multiple myeloma in whom response rates of 40% have been observed after the failure of high-dose therapy followed by stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%